2021
DOI: 10.2172/1819737
|View full text |Cite
|
Sign up to set email alerts
|

Draft Rules for Alloy 617 Creep-Fatigue Design Using an EPP+SMT Approach

Abstract: The report describes an improved new creep-fatigue design method for structural components in high temperature nuclear service. The new method uses an integrated elastic-perfectly plastic (EPP) analysis and Simplified Model Test (SMT) approach that greatly simplifies the design process by avoiding the separate evaluation of creep and fatigue damages and eliminating the requirement of stress classification. The report includes draft design rules, presented in a format compatible with an ASME nuclear Code Case, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…The header model is considered to operate at a constant pressure of 7.5 MPa and 600 • C. The operating time of 5 years is considered in this analysis [32 ].…”
Section: Operating Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The header model is considered to operate at a constant pressure of 7.5 MPa and 600 • C. The operating time of 5 years is considered in this analysis [32 ].…”
Section: Operating Conditionsmentioning
confidence: 99%
“…Figure 10: Variation of temperature in the inner tube of the hot duct during the accident and emergency shutdown, based on a transient heat transfer analysis reported in[32 ].…”
mentioning
confidence: 99%
“…Approaches to account for the primary-load effect on SMT design curves were discussed in Barua et al (2020Barua et al ( , 2021, and the results show that the EPP strain range analysis procedure naturally captures the primary pressure effect. Barua et al (2020Barua et al ( , 2021 also demonstrated that the EPP+SMT methodology is much simpler to execute than conventional CF damage analyses through multiple sample problems. The remaining critical factors in finalizing the SMT-based design curves are the methods for extrapolating the design curves to the low strain range region and with longer hold times (such as long hold time of 1,000 h) that are prototypical of plant operations.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of SMT CF life because of primary load was found to be dependent on strain ranges and elastic follow-up factors. Approaches to account for the primary-load effect on SMT design curves were discussed in Barua et al (2020Barua et al ( , 2021, and the results show that the EPP strain range analysis procedure naturally captures the primary pressure effect. Barua et al (2020Barua et al ( , 2021 also demonstrated that the EPP+SMT methodology is much simpler to execute than conventional CF damage analyses through multiple sample problems.…”
Section: Introductionmentioning
confidence: 99%